Everyday media culture in Africa
1 online resource (xi, 260 pages)
Keywords: African audiences and users are rapidly gaining in importance and increasingly targeted by global media companies, social media platforms and mobile phone operators. This is the first edited volume that addresses the everyday lived experiences of Africans in their interaction with different kinds of media: old and new, state and private, elite and popular, global and national, material and virtual. So far, the bulk of academic research on media and communication in Africa has studied media through the lens of media-state relations, thereby adopting liberal democracy as the normative ideal and examining the potential contribution of African media to development and democratization. Focusing instead on everyday media culture in a range of African countries, this volume contributes to the broader project of provincializing and decolonizing audience and internet studies.